Some Similarity between Contractions and Kannan Mappings - Kikkawa, Misako; Suzuki, Tomonari (Fixed point theory and applications (Hindawi Publishing Corporation), 2008)
Contractions are always continuous and Kannan mappings are not necessarily continuous. This is a very big difference between both mappings. However, we know that relaxed both mappings are quite similar. In this paper, we discuss both mappings from a new point of view.